Federalism and economic reform : international perspectives - Srinivasan, T. N., 1933-2018; Wallack, Jessica Seddon (Cambridge University Press, 2006)
This book contains case studies of economic reform in eight developing and industrial federal countries - Argentina, Australia, Brazil, Canada, China, India, Mexico, and Nigeria. It focuses on the way in which the division of authority between levels of government affects the policymaking process.